Successful osimertinib rechallenge after osimertinib-induced pneumonitis in a patient with lung adenocarcinoma. (2018) - Satoh, Shingo; Shiroyama, Takayuki; Tamiya, Motohiro; Nasu, Shingo; Tanaka, Ayako; Morita, Satomu; Morishita, Naoko; Suzuki, Hidekazu; Okamoto, Norio; Hirashima, Tomonori
Abstract: Pneumonitis is a serious adverse event of EGFR-TKI treatment. Although several cases of EGFR-TKI rechallenge after EGFR-TKI-induced pneumonitis have been reported, little is known about post-pneumonitis osimertinib rechallenge. We describe a 69-year-old never-smoking Japanese woman with postoperative recurrent lung adenocarcinoma retreated with osimertinib after osimertinib-induced pneumonitis. Although osimertinib rechallenge must be carefully chosen based on risk/benefit analysis, osimertinib rechallenge after osimertinib-induced pneumonitis may be an option, with limited alternative therapeutic options.